Hepcidin gene polymorphisms and iron overload in β-thalassemia major patients refractory to iron chelating therapy - Parinaz Zarghamian; Azita Azarkeivan; Ali Arabkhazaeli; Ahmad Mardani; Majid Shahabi (BMC, 2020)
Abstract Background β Thalassemia is one of the most common groups of hereditary haemoglobinopathies. Affected people with thalassemia major are dependent on regular blood transfusion which on the long term leads to iron overload. Hepcidin is a peptide hormone and an important regulator of iron homeostasis, especially in thalassemia. Expression of this hormone is influenced by polymorphisms within the hepcidin gene, HAMP. Several studies emphasized the role of single nucleotide polymorphisms (SNPs) located in the promoter region of the gene. This study aimed to analyze the association between three SNPs in promoter of HAMP, c.-582A > G, c.-443C > T, and c.-153C > T, with iron overload in β-thalassemia major patients. Methods A total of 102 samples from β thalassemia major patients were collected. Genomic DNA was extracted and segments of DNA encompassing rs10421768 and rs142126068 were sequenced. Statistical analysis was performed by SPSS Statistics 23 using independent t test and Fisher's exact test. Results A total of 102 adult β-thalassemia major patients were genotyped for three SNPs in the promoter region of HAMP gene by PCR and direct sequencing. Most of the patients (71.3%) were iron overloaded (based on plasma ferritin > 1000 ng/ml) in spite of receiving regular iron-chelating therapy. Our analysis revealed a statistically significant difference between the level of cardiac iron accumulation and c.-582A > G variant (p = 0.02). For c.-443C > T statistical analysis was on the edge of the significant relationship between the minor allele and serum ferritin (p = 0.058). All samples were homozygous for allele C of c.-153C > T. Conclusions Despite chelating therapy, iron overload is still one of the main complications of thalassemia. Our findings and others emphasize the role of hepcidin -582A > G polymorphism as a key component of iron homeostasis in these patients.